Bebidas alcoólicas e seus riscos. Uma abordagem investigativa para o ensino médio - Breno Carvalho Brito (2022)
The consumption of alcoholic beverages by young people and its implications for mental and physical health has been the object of study and concern by parents, teachers, governments and the scientific community. In this sense, through discussions and experiments proposed by the students themselves, this work aimed at a practical experience of how to observe the effects of ethanol on organic molecules, cells, tissues and organs, making a correlation with the health and the impacts on the life of the individuals. This didactic sequence was composed of an initial moment where the theme was approached and con-textualized, then the students elaborate hypotheses, proposed and performed experiments, presented and discussed the results and elaborated informative material, to clarify problems related to the ingestion of alcoholic beverages. The project was applied to students from two classes of the second year of high school, aged between 15 and 18 years, from a state school located in the city of Belo Horizonte, MG, where the researcher is based. Three products were generated: a Didactic Sequence, a booklet intended for teachers who want to create educational videos and five short videos, with the main concepts covered.